2009
DOI: 10.1074/jbc.m801861200
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-D-aspartate Receptor Subunits Are Non-myosin Targets of Myosin Regulatory Light Chain

Abstract: Excitatory synapses contain multiple members of the myosin superfamily of molecular motors for which functions have not been assigned. In this study we characterized the molecular determinants of myosin regulatory light chain (RLC) binding to two major subunits of the N-methyl-D-aspartate receptor (NR). Myosin RLC bound to NR subunits in a manner that could be distinguished from the interaction of RLC with the neck region of non-muscle myosin II-B (NMII-B) heavy chain; NR-RLC interactions did not require the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 69 publications
0
35
0
Order By: Relevance
“…Plasmids containing rat GluN2A, GluN2B and GluN1-1a cDNAs, and the construction of GluN1-C0 (834-864), GluN1 (834-938), GluN2A (838-874), GluN2A (875-1029), GluN2A (1030-1464) and GluN2A (838-1464) in pGEX vectors (GE Healthcare, Piscataway, NJ have been described previously [9,10]. GluN2A (991-1029) was amplified by PCR and inserted into pGEX-6P-3 for fluorescence spectroscopy experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmids containing rat GluN2A, GluN2B and GluN1-1a cDNAs, and the construction of GluN1-C0 (834-864), GluN1 (834-938), GluN2A (838-874), GluN2A (875-1029), GluN2A (1030-1464) and GluN2A (838-1464) in pGEX vectors (GE Healthcare, Piscataway, NJ have been described previously [9,10]. GluN2A (991-1029) was amplified by PCR and inserted into pGEX-6P-3 for fluorescence spectroscopy experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Postsynaptic density protein of 95 kDa (PSD-95) and related scaffold proteins bind a common distal ESDV motif [6], whereas the membrane-proximal regions of GluN2A and GluN2B share tyrosine-based recognition motifs for the clathrin-dependent, endocytic adapter protein 2 complex (AP-2) [7,8]. We have previously shown that the same membrane-proximal regions of GluN2A and GluN2B also bind a light chain of the actin-based motor myosin II that likely serves an early trafficking function [9]. As the membrane-proximal regions of the GluN2A and GluN2B C-termini appear to have some functional equivalency, the goal of this study was to analyze the region of GluN2A immediately downstream of the paired endocytic motifs and minimal myosin light chain interaction domain.…”
Section: Introductionmentioning
confidence: 99%
“…These receptors including CXCR4, Ins(1,4,5)P3-R, and NMDA-R are not single transmembrane receptors with the exception of the discoidin domain receptor 1 (DDR1) which is a tyrosine kinase receptor activated by type I collagen (23)(24)(25)(26). The EGFR is identified as an NM II binding partner in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications have reported that NM II interacts with several kinds of receptors including CXCR4 (chemokine receptor), N-methyl-D-aspartate (NMDA receptor), DDR1 (as a collagen receptor), and the Ins (1,4,5)P 3 receptor (23)(24)(25)(26). However, to date, the potential involvement of NM II in EGFRmediated intracellular signaling has not been studied in depth.…”
mentioning
confidence: 99%
“…NMDA receptor reg ulates actin cytoskeleton in at least two ways: (1) by mediating the influx of Ca 2+ ions into postsynaptic neurons, which modulate the activity of many actin binding proteins, e.g., CaMKII (Lisman et al, 2002) and gelsolin (Nag et al, 2009);and (2) by binding directly to actinbinding or regulating proteins, e.g., CaMKII (Raveendran et al, 2009), actinin (Wyszynski et al, 1997), and myosin regulatory light chain (Bajaj et al, 2009). Also, various receptor tyrosine kinases, such as members of the Trk (BDNF receptor; Menna et al, 2009) and Eph/ephrin families (Schubert and Dotti, 2007), as well as synaptic adhesion molecules (Yoshihara et al, 2009), have been shown to be important in regulating actin in spines.…”
Section: Signaling To the Actin Cytoskeleton In Dendritic Spinesmentioning
confidence: 99%